2021
DOI: 10.1007/s11356-021-15929-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate variables on the transmission of COVID-19: a systematic review of 62 ecological studies

Abstract: The new severe acute respiratory syndrome coronavirus 2 was initially discovered at the end of 2019 in Wuhan City in China and has caused one of the most serious global public health crises. A collection and analysis of studies related to the association between COVID-19 (coronavirus disease 2019) transmission and meteorological factors, such as humidity, is vital and indispensable for disease prevention and control. A comprehensive literature search using various databases, including Web of Science, PubMed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…This research was based on the USA, a whole country with a very large geographical area and various weather environments and landforms. Thus, it is difficult for us to find a suitable meteorological index or air pollution index to exactly describe the characteristics of this geographical environment, although meteorological factors and air quality can affect the spread of COVID-19 (Copat et al 2020 ; Zheng et al 2021a , b ). In fact, the occurrence of COVID-19 should be impacted by the spatiotemporal variations especially in large areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was based on the USA, a whole country with a very large geographical area and various weather environments and landforms. Thus, it is difficult for us to find a suitable meteorological index or air pollution index to exactly describe the characteristics of this geographical environment, although meteorological factors and air quality can affect the spread of COVID-19 (Copat et al 2020 ; Zheng et al 2021a , b ). In fact, the occurrence of COVID-19 should be impacted by the spatiotemporal variations especially in large areas.…”
Section: Resultsmentioning
confidence: 99%
“…XGBoost has also been used in other diseases for disease prediction and risk factor analysis, such as smoking-induced noncommunicable disease (Davagdorj et al 2020 ) and kidney disease (Chen et al 2019 ). The Light Gradient Boosting Machine (LightGBM) model showed better discrimination ability than the traditional model in predicting the all-cause mortality of patients (Zheng et al 2021a , b ), but it has not been used in COVID-19 prediction. To date, none of these three methods has been used to forecast daily cases of COVID-19 in the USA, which is one of the innovations in our research.…”
Section: Introductionmentioning
confidence: 99%
“…Newly discovered SARS-CoV and SARS-CoV-2 infections also started in winter months. In addition, some reports support the seasonal nature of SARS-CoV-2 [46,47]. However, it cannot be pointed out that climatic parameters such as temperature or humidity alone play a central role during the pandemic [48].…”
Section: Seasonality Of Covid-19mentioning
confidence: 99%
“…Therefore, this study focused on whether measurable risk variables could be found through global COVID-19 data in order to implement epidemic control more efficiently in China. Previous studies [12] , [13] , [14] , [15] , [16] about the association between COVID-19 transmission and meteorological conditions have been published over the last years. However, diversity of selected regions, data sets, and mathematical methods might contribute to specific results, leading to significantly different from each other [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%